Trade contestation and regional politics: The case of Belgium and Germany - Egan, Michelle; Guimarães, Maria Helena (Frontiers in Political Science, 2022)
In developing an extensive network of trade agreements, the European Union has pushed for liberalization commitments that impinge on the competencies of subnational jurisdictions. This raises new challenges in federal systems as the emerging multilevel character of trade politics means subnational authorities could increasingly demand a say in the negotiation or ratification of these trade agreements. To address the tension between subnational regulatory autonomy and collective problem-solving in trade negotiations, Europe needs to avoid suboptimal trade outcomes where actions of contestation by subnational jurisdictions on the grounds of regulatory encroachment can undermine or veto collective agreement. Using the cases of Belgium and Germany, this article illustrates how the growing subnational contestation around trade agreements requires greater coordination and consensus to avoid domestic gridlock in their ratification. The article suggests normative ideas for the EU to address the overlapping authority challenges across multilevel governance. As the values of trade have changed, these normative measures should include the framing of trade narratives, addressing asymmetries of influence, enhancing subnational engagement, and mitigating the distributive costs of liberalization. These avenues for trade policymaking are to be ultimately advantageous for the EU's pursuit of greater integration.